Essentials and pertinence of cold plasma in essential oils, metal–organic frameworks and agriculture - Khan, Mujahid Ameen; Akram, Sumia; Naeem, Rabia; Kamal, Muhammad Umair; Muhammad, Gulzar; Mushtaq, Muhammad; Anwar, Farooq; Bandegharaei, Ahmad Hosseini (Wiley, 2024)
Cold atmospheric pressure plasma (CAPP) comprises an ensemble of ionized gas, neutral particles, and/or reactive species. Electricity is frequently used to produce CAPP via a variety of techniques, including plasma jets, corona discharges, dielectric barrier discharges, and glow discharges. The type and flow rates of the carrier gas(es), temperature, pressure, and vacuum can all be altered to control the desired properties of the CAPP. Since a few decades ago, CAPP has become a widely used technology with applications in every walk of life. The plasma activated liquid mediums like water, ethanol, and methanol have been merged as novel sterilizers. With recent advancements in material science, particularly work on metal–organic frameworks (MOFs), essential oils, and agricultural technologies, CAPP has become a vital component of these advancements. Likewise, CAPP has been found as a green and benign technology to induce early seed germination and plant development. This review covers the critical components of CAPP, the production of reactive oxygen and nitrogen species, and mechanisms by which CAPP-based technologies are applied to agricultural products, MOFs, and essential oils.